Transcutaneous Electrical Acupoint Stimulation Combined With Auricular Acupressure Reduces Postoperative Delirium Among Elderly Patients Following Major Abdominal Surgery: A Randomized Clinical Trial - Fan, Qianqian; Lei, Chong; Wang, Yonghui; Yu, Nannan; Wang, Lini; Fu, Jingwen; Dong, Hailong; Lu, Zhihong; Xiong, Lize (Frontiers in Medicine, 2022)
Background Postoperative delirium is common in elderly patients following major surgery. This study aimed to assess the effect of transcutaneous electrical acupoint stimulation combined with auricular acupressure on the incidence of postoperative delirium among older patients undergoing major abdominal surgery. Methods In this single-center, randomized controlled clinical trial, 210 patients aged 65 years or older undergoing major abdominal surgery were randomized to receive either intervention treatment (transcutaneous electrical acupoint stimulation started at 30 min before anesthesia until the end of the surgery, followed by intermittent auricular acupressure in the first three postoperative days; n=105) or standard care (n=105). The primary outcome was the incidence of delirium at the first seven postoperative days or until hospitalization depended on which came first. Secondary outcomes included delirium severity, opioid consumption, postoperative pain score, sleep quality, length of postoperative hospital stay, and postoperative 30-day complications. Enrollment was from April 2019 to March 2020, with follow-up ending in April 2020. Results All of the 210 randomized patients (median age, 69.5 years, 142 [67.6%] male) completed the trial. The incidence of postoperative delirium was significantly reduced in patients received intervention treatment (19/105 (18.1%) vs. 8/105 (7.6%), difference, -10.5% [95% CI, –1.5% to –19.4%]; hazard ratio, 0.41; 95% CI, 0.18 to 0.95; P= 0.023). Patients in the control group had a higher postoperative Memorial Delirium Assessment Scale (4 vs.3; difference, –1; 95% CI, –1 to 0; P=0.014) and a greater increase in Pittsburgh Sleep Quality Index score from baseline to postoperative day three (2.5 vs. 2.0; difference, –1; 95% CI, –2 to –1; P< 0.001) than patients in the intervention group. No significant difference was observed as of other secondary outcomes. Conclusions In elderly patients undergoing major abdominal surgery, transcutaneous electrical acupoint stimulation combined with auricular acupressure reduced the incidence of postoperative in-hospital delirium compared with standard care. A multicenter, randomized clinical trial with a larger sample size is necessary to verify these findings.